2008
DOI: 10.1164/rccm.200712-1876oc
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia Predicts Right Heart Failure and Poor Survival in Pulmonary Arterial Hypertension

Abstract: Rationale: Hyponatremia is associated with decompensated heart failure and poor prognosis in patients with left ventricular systolic dysfunction. Objectives: We sought to determine if hyponatremia is associated with right heart failure and worse prognosis in patients with pulmonary arterial hypertension (PAH). Methods: We prospectively followed 40 patients with PAH and examined the relationship between serum sodium and right heart function as well as survival. Measurements and Main Results: Subjects with hypon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 25 publications
4
110
2
1
Order By: Relevance
“…Hyponatraemia is a well established prognostic factor in LHF [18,21,22], and has been attributed to neurohormonal activation mediated mostly by vasopressin and causing water retention. We have previously demonstrated that hyponatraemia is a strong indicator of poor long-term survival in patients with PAH [5]. In the current cohort, hyponatraemia was strongly associated with low SBP, which was itself a significant predictor for in-hospital mortality, suggesting mediation by neurohormonal activation in the context of low cardiac output.…”
Section: Course and Outcomes For Rhf Hospitalisationsupporting
confidence: 50%
See 2 more Smart Citations
“…Hyponatraemia is a well established prognostic factor in LHF [18,21,22], and has been attributed to neurohormonal activation mediated mostly by vasopressin and causing water retention. We have previously demonstrated that hyponatraemia is a strong indicator of poor long-term survival in patients with PAH [5]. In the current cohort, hyponatraemia was strongly associated with low SBP, which was itself a significant predictor for in-hospital mortality, suggesting mediation by neurohormonal activation in the context of low cardiac output.…”
Section: Course and Outcomes For Rhf Hospitalisationsupporting
confidence: 50%
“…The estimated glomerular filtration rate (eGFR) was calculated from creatinine values using the Modified Diet in Renal Disease equation [11]. Hyponatraemia was defined as serum Na f136 mEq?L -1 based on previous literature on PAH [5] and LHF [12,13].…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong correlation between hyponatremia, as a marker of neurohormonal activation, and RV dysfunction and survival was demonstrated in a cohort of patients with PAH (23), where patients with SSc-PAH were more likely to be hyponatremic than patients with IPAH despite similar hemodynamics, suggesting possible differences in neurohormonal activation between the two groups. These as well as other specific markers of disease and disease severity should be identified.…”
Section: Assessing Markers Of Severitymentioning
confidence: 94%
“…In left-heart disease, data suggest that these abnormalities are linked to survival [33], and it has been recently found that hyponatraemia is predictive of poor survival for PAH patients in stable condition. The pathophysiological mechanisms have been proposed to mirror those in left-heart failure [34]. Some studies have tested the efficacy of specific therapeutic interventions antagonising the vasopressin pathway in left-heart failure (outside the ICU setting), showing an improvement in serum level of sodium and dyspnoea, but no change in survival [35,36].…”
Section: Pulmonary Circulation and Pulmonary Vascular Diseasementioning
confidence: 99%